The Go Programming Language and Environment. - COX, RUSS; GRIESEMER, ROBERT; PIKE, ROB; TAYLOR, IAN LANCE; THOMPSON, KEN (Communications of the ACM, 2022)
The article discusses the computer programming language known as Go, which was created at the high technology firm Google in 2007, and open source released in 2009. It examines the decision making processes concerning the design and success of Go, how Go treats language features, and the March 2022 release of Go 1.18.